Water allocation with use of the Building Block Methodology (BBM) in the Godavari Basin, India - Bakken, T.H.; Skarbovik, E.; Gosain, A.K.; Kuppannan, Palanisami; Sauterleute, J.; Egeland, Helene; Kakumanu, Krishna Reddy; Sekhar, N.U.; Harby, A.; Tirupataiah, T.; Stalnacke, P. (2013)
Access to sufficient quantities of water of acceptable quality is a basic need for human beings and a pre-requisite to sustain and develop human welfare. In cases of limited availability, the allocation of water between different sectors can result in conflicts of interests. In this study, a modified version of the Building Block Methodology (BBM) was demonstrated for allocation of waters between different sectors. The methodology is a workshop-based tool for assessing water allocation between competing sectors that requires extensive stakeholder involvement. The tool was demonstrated for allocation of water in the Sri Ram Sagar water reservoir in the Godavari Basin, Andhra Pradesh, India. In this multipurpose reservoir, water is used for irrigation, drinking water supply and hydropower production. Possible water allocation regimes were developed under present hydrological conditions (normal and dry years) and under future climate change, characterized by more rain in the rainy season, more frequent droughts in the dry season and accelerated siltation of the reservoir, thus reducing the storage capacity. The feedback from the stakeholders (mainly water managers representing the various sectors) showed that the modified version of the BBM was a practical and useful tool in water allocation, which means that it may be a viable tool for application also elsewhere.